Implementation Machine Learning Algorithms To Predict The Financial Resilience Of Companies Based On Financial Statements - Nadya Andhika Putri; Nico Gawa Lahara (Jurnal Sains Informatika Terapan, 2025)
This study explores the application of machine learning algorithms to predict the financial resilience of companies based on their financial statements. In an era of data-driven decision-making, traditional financial analysis methods may fall short in providing timely and accurate insights. By leveraging advanced machine learning techniques, such as regression models, decision trees, and neural networks, this research aims to create predictive models that can effectively forecast a company's financial health. The study utilizes historical financial data, including balance sheets, income statements, and cash flow reports, to train and test various machine learning models. The findings highlight the potential of machine learning in identifying patterns and trends within financial data that may not be readily apparent through conventional methods. The results can provide valuable tools for financial analysts, investors, and company managers to assess and mitigate financial risks, enhancing decision-making processes and strategic planning